REPRESENTASI HATARAKISUGI DALAM VIDEO KLIP ROBOT - Sintyadewi, Ni Putu Lisa (Humanis; Volume 14. No.1. Januari 2016, 2016)
This study entitled "Representation of Hatarakisugi in Video Clip Robot". This study aims to determine representation of hatarakisugi and the message contained in the video clip Robot. Based on the analysis that has been found, hatarakisugi experienced by the main character in the video clip Robots can be classified into a workaholic type of dyed in the wool. Hatarakisugi behavior represented on verbal and visual markin the video clip Robot. Hatarakisugi verbal representations include (1) lack of social life, (2) professional attitude, (3) loyalty to the job and (4) excessive working hours. Hatarakisugi visual representations include (1) a lack of social life, (2) ???? (noukiGenshu), (3) excessive working hours, and (4) loyalty to the job. Messages contained in the video clip Robot include (1) life need to socialize, (2) should be able to share time with good, (3) Work in a professional manner, (4) be smart health care,and (5) finish the job on time.
Keywords: representation, hatarakisugi, sign